2003
DOI: 10.1002/prot.10282
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for structural proteomics of prokaryotes: Quantifying the advantages of studying orthologous proteins and of using both NMR and X‐ray crystallography approaches

Abstract: Only about half of non-membrane-bound proteins encoded by either bacterial or archaeal genomes are soluble when expressed in Escherichia coli (Yee et al., Proc Natl Acad Sci USA 2002;99:1825-1830; Christendat et al., Prog Biophys Mol Biol 200;73:339-345). This property limits genome-scale functional and structural proteomics studies, which depend on having a recombinant, soluble version of each protein. An emerging strategy to increase the probability of deriving a soluble derivative of a protein is to study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 23 publications
2
60
0
Order By: Relevance
“…The above provides a strong motivation for further research and development in this area. Several strategies have been proposed to improve the success rate including obtaining one representative structure per protein family and working with multiple orthologues [14,26,27,28].…”
Section: X-ray Crystallography and Protein Crystallizationmentioning
confidence: 99%
“…The above provides a strong motivation for further research and development in this area. Several strategies have been proposed to improve the success rate including obtaining one representative structure per protein family and working with multiple orthologues [14,26,27,28].…”
Section: X-ray Crystallography and Protein Crystallizationmentioning
confidence: 99%
“…This study suggests that the choice of affinity tag is as important as the decision to retain the tag. A third study tested 49 proteins with and without His 6 tags: 11 proteins crystallized both with and without the tag, 9 crystallized only without a tag and 7 crystallized only with a tag [21]. In conclusion, many small affinity tags are compatible with crystallization, and they sometimes enable crystallization.…”
Section: Target Selection and Constructsmentioning
confidence: 97%
“…One HTGS project found that the species of origin made a large difference in the ability to crystallize particular proteins. The crystallization success rate for 62 different proteins from Escherichia coli and Thermotoga maritime were 26 and 32 %, respectively [21]. But 90 % of the proteins crystallized were only crystallized from one of the two organisms.…”
Section: Target Selection and Constructsmentioning
confidence: 99%
“…Once protein partners have been identified, these proteins can be coexpressed and copurified with their interacting partner. Orthologous proteins from many different species can be tested simultaneously and the best behaving proteins will then be selected for further examination (Savchenko et al, 2003). Similarly, protein engineering by introducing random or directed single point mutations can be used to improve protein properties like stability and solubility.…”
Section: Validation Of the Pipeline And Outlookmentioning
confidence: 99%